Over There. - Lennon, J. Robert (GRANTA)
Presents analogies of the state of the world with the United States as the leader. View of the world as a dysfunctional family with the U.S. as the father and Iraq as the lawn that needs to be cleaned; Metaphor showing America as the zookeeper and countries such as Great Britain and Germany as the assistant zookeepers; Description of the world as a computer with America as the operating system, with other countries as programs that run on the operating system.